2018
DOI: 10.1177/0271678x18814614
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of hypothermia on neurovascular unit determine protective or toxic results: Toward optimized therapeutic hypothermia

Abstract: Therapeutic hypothermia (TH) benefits survivors of cardiac arrest and neonatal hypoxic–ischemic injury and may benefit stroke patients. Large TH clinical trials, however, have shown mixed results. Given the substantial pre-clinical literature supporting TH, we explored possible mechanisms for clinical trial variability. Using a standard rodent stroke model ( n = 20 per group), we found smaller infarctions after 2 h pre- or post-reperfusion TH compared to 4 h. To explore the mechanism of this discrepancy, we us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 69 publications
0
60
0
2
Order By: Relevance
“…We used a very small sample size in this proof-of-concept study; however, confirmatory studies are being planned with a recent grant application to the National Institutes of Health. Recently, Lyden et al 18 have predicted that rapid short duration of deep TH may be beneficial over delayed lengthy TH. The large animal model presented here would be well suited to investigate further these findings; however, due to the scope of our preliminary study, we were not able to include a control group of delayed long duration TH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used a very small sample size in this proof-of-concept study; however, confirmatory studies are being planned with a recent grant application to the National Institutes of Health. Recently, Lyden et al 18 have predicted that rapid short duration of deep TH may be beneficial over delayed lengthy TH. The large animal model presented here would be well suited to investigate further these findings; however, due to the scope of our preliminary study, we were not able to include a control group of delayed long duration TH.…”
Section: Discussionmentioning
confidence: 99%
“…The whole-body or systemic TH approach is limited by the long time required to achieve a therapeutic decrease in temperature and associated negative side effects 7 13–17. A recent study has suggested that rapid deep cooling for a short duration may be superior to longer durations of TH, as the latter may decrease the paracrine support of neurons during injury by astrocytes 18. However, the length of time to deep TH is limited by a whole-body cooling approach.…”
Section: Introductionmentioning
confidence: 99%
“…We sought to confirm thrombin's astrocyte‐activating effect by adding thrombin onto stable, nonischemic, cultured rat astrocytes. In pilot experiments, we demonstrated the effect of various OGD times and several thrombin doses on cultured rat neurons and astrocytes (Figure S5): 80% of neurons and astrocytes were killed by 2 or 8 hr of OGD, respectively (Lyden et al, ). Cultured rat astrocytes did not express prothrombin (Figure S6).…”
Section: Resultsmentioning
confidence: 99%
“…Each coverslip was divided into four quadrant and 12–14 images at 10× resolution were captured from each quadrant. GFAP and Serpin‐A3N florescence intensity was quantified using NIH Image J software as described previously (Lyden et al, ) (version 1.51).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation